Pitfalls of Teachers on Modular Distance Learning: Basis for a Proposed Action Plan - Rolando R. Mairina; Domingo M. Cabarteja; Jeger P. Paragas (Universal Journal of Educational Research)
The study was conducted to determine the pitfalls encountered by grade five teachers during modular teaching and learning. Specifically, it aimed to find out the pitfalls encountered by teachers along with students’ comprehension, students’ academic behavior, monitoring of students’ education, and physical interaction with the learners. The personal profile of teachers, out of the total respondents (56), most of the teachers are female-dominated. Most of them belong to the age bracket of 34 to 45 and most of the teachers are married. Most of the teachers had attended post-graduate studies. Most respondents are still young in the service, holding Teacher 2 and Teacher 3 positions, and attending local, national, and regional training. On the level of pitfalls encountered by teachers in modular teaching and learning, most respondents experienced a slight gravity level in the four aspects. The computed average weighted mean along comprehension is 2.50, along academic behavior is 2.54, along monitoring of students’ performance is 2.58, and along physical interaction is 2.79. All have an equivalent value of moderately grave. There is a specific profile of teachers that is significantly related. Age is significantly associated with monitoring students’ learning. The computed r value is .270, while the calculated significance level is 0.04. Training attended by the teachers is significantly related to some aspects of students’ comprehension, (computed sig. value is 0.04 and physical interaction is .02), which is lower than the .05 level of significance. The grade five teachers who served as respondents are mostly female dominated; they are in their early forties and married. Most of them are attending post-graduate studies and have attended relevant training. Second, the level of teachers’ pitfalls is mostly moderately grave. In addition, age is significantly related to monitoring, training is significantly associated substantially with physical interaction and comprehension.